Role of cytohormonal study in normal pregnancy and in threatened abortion - Patil, Shailesh B.; Patil, Milind B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: It is certain from clinical experience of many that one or more hemorrhages in early pregnancy can still end up in good fetal outcome. So, our study deals with comparison of cytohormonal study in pregnancy and threatened abortion. The study was conducted with the aim of utilizing colpocytogram as a tool in assessing and treating cases of threatened abortion and comparing them with normal pregnant women. Methods: Patients attending antenatal care unit on outdoor basis and labelled as normal pregnancy cases were considered as control group. The patients of threatened abortion were studied when they were admitted in Gynecology department for indoor treatment. Patients were studied taking into consideration their age, parity, number of abortions, complaints (P/V bleeding, pain in abdomen), gestational age, per abdomen and per vaginal findings and also USG findings and vaginal smear pattern. Results: Maximum number of patients was present in the age group of 21-25 years in both the groups. While only 13.33% had normal smear pattern in threatened abortion group. 86.67% patients in threatened abortion group showed abnormal smear pattern. There is statistically significant difference was found (p<0.05). There is statistically significant was found (P<0.01) and indicates good effects of the drug on the vaginal epithelium. Conclusions: The cytohormonal study acts as a simple, reliable, good, noninvasive method for evaluation of hormonal pattern in normal pregnancy and threatened abortion.